2015
DOI: 10.1001/jamainternmed.2014.6353
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Worker Home Visits for Adults With Uncontrolled Asthma

Abstract: IMPORTANCE Asthma is often poorly controlled. Home visitation by community health workers (CHWs) to improve control among adults has not been adequately evaluated. OBJECTIVE To test the hypothesis that CHW home visits for adults with uncontrolled asthma improve outcomes relative to usual care. DESIGN, SETTING, AND PARTICIPANTS Randomized parallel group study with 1-year follow-up, conducted 2008 through 2011 at homes of low-income adults aged 18 to 65 years with uncontrolled asthma living in King County, Washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(105 citation statements)
references
References 48 publications
1
103
0
1
Order By: Relevance
“…These findings align with previous research on the value of patient navigation for patients with chronic disease, including improved asthma control and quality of life for children and adults (Crocker et al, 2011;Krieger et al, 2015;Krieger et al, 2009), reduced disparities in adult cancer diagnosis and care (Perez-Escamilla et al, 2015), and improved bloodglucose control for Latino adults with type 2 diabetes (Rodday et al, 2015). Apart from these benefits for pediatric asthma care, however, we did not see across-the-board improvements in all trigger and medication-related practices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings align with previous research on the value of patient navigation for patients with chronic disease, including improved asthma control and quality of life for children and adults (Crocker et al, 2011;Krieger et al, 2015;Krieger et al, 2009), reduced disparities in adult cancer diagnosis and care (Perez-Escamilla et al, 2015), and improved bloodglucose control for Latino adults with type 2 diabetes (Rodday et al, 2015). Apart from these benefits for pediatric asthma care, however, we did not see across-the-board improvements in all trigger and medication-related practices.…”
Section: Discussionsupporting
confidence: 89%
“…Despite research documenting the benefits of patient navigators for chronic disease management, we know little about how these benefits are actually realized, including assisting caregivers with asthma management in children (Crocker et al, 2011;Krieger, Song, & Philby, 2015;Krieger, Takaro, Song, Beaudet, & Edwards, 2009;Perez-Escamilla et al, 2015;Rodday et al, 2015). In this study we aim to help explore this issue by complementing MCAN evaluation findings with caregivers' perceptions of the factors and conditions by which patient navigators support their effective management of their child's asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase. 46 …”
Section: Emergency Department Visitsmentioning
confidence: 93%
“…58 Of the four RCTs measuring preventable use, three found a statistically significant decrease relative to a control. 40,54,59 Three pre-post studies found a decrease in preventable use relative to baseline. 43,45,46 One cohort study found no change in emergency medication use, 49 while another (the only study that measured medication costs) noted a significant decrease in nonnarcotic prescription costs for the control cohort relative to the CHW group.…”
Section: Medication Usementioning
confidence: 99%
“…[3][4][5][6] Interventions by CHWs supporting chronic disease self-management and preventive services show improved health care utilization, knowledge, self-care, adherence, health outcomes, and quality of life, particularly when these workers are integrated into primary care teams. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] Their interventions are most often directed to and studied in underserved communities (racial and ethnic minority and low-income populations, federally qualified health care [FQHC] settings), where the integration of these workers show benefit. 3,4,12,[21][22][23] Health authorities have called for expanding interventions by CHWs among clinics serving these populations, and recent policies create a platform for greater community health worker integration.…”
mentioning
confidence: 99%